1998
DOI: 10.1021/ja971415w
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Action of Vitamin B12. Ultrafast Radical Clocks Provide No Evidence for Radical Intermediates in Cyclopropane Models for the Methylmalonyl-CoA to Succinyl-CoA Carbon Skeleton Rearrangement

Abstract: To probe for free radical intermediates in the model studies for the coenzyme B12-dependent, methylmalonyl-CoA to succinyl-CoA carbon-skeleton rearrangement, new models incorporating cyclopropane rings (unsubstituted 23 and 2-phenyl-substituted 28) at the 2-position were developed. The reaction of 23 or 28 with vitamin B12s gives only rearranged succinate 24 or 29, respectively, with the cyclopropyl group intact. When this reaction was carried out in EtOD/D2O, a monodeuterided product, 24- d 1 or 29- d … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 25 publications
0
17
0
Order By: Relevance
“…In the next step, an interchange of the carbonyl-CoA group and a hydrogen atom occurs between vicinal carbons. The precise mechanism by which the substrate radical isomerizes to the product radical is unresolved, with pathways involving free radical intermediates (3), fragmentation products (11), carbocations (12), carbanions (13), and organocobalt adducts (14,15), each having been proposed (Scheme II). The final step involves reabstraction of a hydrogen atom from deoxyadenosine to generate product and the intact cofactor, AdoCbl.…”
mentioning
confidence: 99%
“…In the next step, an interchange of the carbonyl-CoA group and a hydrogen atom occurs between vicinal carbons. The precise mechanism by which the substrate radical isomerizes to the product radical is unresolved, with pathways involving free radical intermediates (3), fragmentation products (11), carbocations (12), carbanions (13), and organocobalt adducts (14,15), each having been proposed (Scheme II). The final step involves reabstraction of a hydrogen atom from deoxyadenosine to generate product and the intact cofactor, AdoCbl.…”
mentioning
confidence: 99%
“…8). For reactions catalyzed by 2-methyleneglutarate mutase, methylmalonyl-CoA mutase and related acyl-CoA mutases, the inter-conversion of substrate and product radicals most likely occurs through a cyclopropylcarbenyl radical intermediate, a mechanism supported by model chemical reactions [23,24]. In contrast, it has been shown that the rearrangement catalyzed by glutamate mutase involves fragmentation of the glutamyl radical to form a glycyl radical and acrylate followed by recombination to form the methylaspartyl radical [25].…”
Section: Mechanistic Overviewmentioning
confidence: 99%
“…8). Neither species has been directly observed in the enzyme, although studies on model compounds support the latter mechanism [23]. Using the rearrangement of the 3-propanal radical as a minimal model for the methylmalonyl-CoA mutase reaction, the addition-elimination mechanism was found to be the more favorable mechanism by ~12 kcal/mol.…”
Section: Computational Studies Of Adocbl Enzymesmentioning
confidence: 99%
“…For the reactions catalyzed by methylmalonyl-CoA mutase,[14, 74] isobutyryl-CoA mutase [75] and 2-methyleneglutarate mutase [9, 76] the inter-conversion of substrate and product radicals can occur through a cyclopropylcarbenyl radical intermediate (figure 4), a mechanism supported by model chemical reactions. [77, 78] In contrast, the rearrangement catalyzed by glutamate mutase [18, 19, 79] cannot occur through this type of intermediate and it has been shown experimentally that the mechanism involves fragmentation of the glutamyl radical to form a glycyl radical and acrylate followed recombination to form the methylaspartyl radical. [80]…”
Section: Catalytic Reactions Of Adenosyl Radicalmentioning
confidence: 99%